068 The effect of heart failure on apelin mediated vasodilatation. (22nd September 2015) - Dalzell, JR; Rocchiccioli, JP; Padmanabhan, N; Myles, RC; Jackson, CE; Smith, GL; Petrie, MC; McMurray, JJV
Abstract : Background: The novel peptide apelin is the endogenous ligand for the APJ receptor and both are ubiquitously expressed throughout the cardiovascular system. Apelin has diuretic and inotropic actions and is a nitric oxide(NO)-dependent vasodilator. Plasma and myocardial apelin levels are reduced in heart failure (HF). Apelin may therefore have therapeutic value in HF. The effect of HF on the vasoactive properties of apelin is unknown. We compared the vasodilator action of apelin in mesenteric arteries from rabbits with and without HF. Methods: Mesenteric arteries were obtained from normal control (26 vessels/13 rabbits) and HF (27/14) male New Zealand white rabbits. HF was induced by left anterior descending coronary artery ligation. Mean ejection fraction of the HF rabbits was 40.36% (SD 5.26). Arterial segments were isolated and mounted on a 4-channel myograph. Vessels without intact endothelium were discarded. Following pre-constriction with norepinephrine, cumulative concentration–response curves were constructed for apelin (pyr1-apelin-13) and acetylcholine (both 3×10 −9 M - 3×10 −5 M). Results: Apelin produced concentration-dependent relaxation in MAs from healthy rabbits with 45.7 (SEM 9.24)% relaxation at maximum dose. This vasodilator action of apelin was significantly attenuated in MAs from rabbits with HF (max relaxation 4.52(SEM 4.44)%, p<0.01). There was no significant difference to the maximal response to acetylcholine in healthy and HF rabbits (max relaxation healthy 85.4 (SEM 2.54)%; HF 72.85 (SEM 7.38)%, p=0.13). Conclusion: The vasodilator action of apelin is virtually abolished in HF. The loss of response to apelin but not to acetylcholine suggests a specific apelin-APJ system abnormality as opposed to a general diminution of NO-mediated vasodilatation. Myocardial APJ receptor downregulation has been reported in animal and human models of HF and further work is required to establish if our results represent a functional consequence of APJ downregulation in the vasculature.